(untitled) (Journal Pharmasci (Journal of Pharmacy and Science), 2024)
The combination of alpha arbutin and niacinamide is often used in facial whitening creams at relatively small levels so required valid analysis method. This study aimed to develop HPLC method for analyzing alpha arbutin and niacinamide in three brands of whitening creams. The HPLC system developed was a reverse phase type with a C?? column and the mobile phase was a mixture of metanol: aquabidest (20:80, v/v) with a flow rate of 1.0 ml/min and a detection wavelength of 274 nm. The results showed that all parameters met the requirements. The linearity test yielded a correlation value was r= 0.999. The LOD value for alpha arbutin was 0.405 µg/mL and the LOD for niacinamide was 0.398 µg/mL. The LOQ value of alpha arbutin was 1.351 µg/mL, the LOQ for niacinamide was 1.327 µg/mL and the selectivity was good. Precision test results with %RSD ? 2% and accuracy tests yielded values in the 99.04-100.97% range. The content of alpha arbutin in brand A was 0.651%, brand B was 0.551%, and brand C was 0.878%. The content of niacinamide in brand A was 0.526%; brand B was 0.680% and brand C was 1.053%. The results of the analysis meet the requirements.